Analisis Strategi Pemasaran untuk Meningkatkan Pendapatan UMKM - Ery Suryanti; Hendra Lesmana; Husni Mubarok (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
Marketing is an activity in which a business actor offers his product to consumers in order to receive the product with all ideas and ideas so that the product can be sought after by consumers. Marketing is an important element that must be considered so that it is in line with expectations, which is to get the expected consumers. Various types of MSMEs that stand and various types of products offered from all that exist are almost the same because MSME products are easy to make with materials that are not so expensive. Of the many types of products that exist MSMEs need more creative innovation so consumers can be interested because there are types of products that are almost every day the same so here it is necessary to have the courage to create products that cannot be competed. Using a SWOT analysis can find out how the marketing strategy is right on target. Includes internal factors, namely strengths and weaknesses and external factors, namely opportunities and threats that are owned by MSMEs. As well as knowing the objectives of the marketing strategy used so that it can increase revenue with many consumers interested in the product being sold. Data collection techniques through documentation, interviews and observations. Data analysis techniques used research documentation and descriptive analysis.